Cardiac Autonomic Neuropathy In Relation To Cardiovascular Reflex Tests and QTc Prolongation In Diabetes Mellitus: Cardiac Autonomic Neuropathy In Relation To Cardiovascular Reflex Tests and QTc Prolongation In Diabetes Mellitus - U, Gandhi Archana; P, Patel Hiren; V, Patel Sangita; Y, Kadam Abhishek; M, Parmar Vidhi (National Journal of Integrated Research in Medicine, 2018)
Background and objectives: Cardiac autonomic neuropathy (CAN) contribute to the poor prognosis of Coronary heart disease (CHD) and Congestive heart failure (CHF) in diabetes. This study was done to evaluate the prevalence of cardiac autonomic neuropathy in diabetic patients by cardiovascular reflex tests and to investigate relation between QTc prolongation and cardiac autonomic neuropathy (CAN).Methods: The study was conducted at the Department of Internal Medicine, Medical College, Baroda by selecting 70 documented diabetic patients as per criteria recommended by the American diabetes association (ADA). Patients were subjected to different cardiovascular reflex tests and ECG was done to calculate corrected QT interval. Statistical analysis was done with help of epi info software. Results: In this study, definitive CAN was found in 34 (49%) cases with early CAN in 27(39%) and severe CAN in 7(10%) of diabetic patients. Most affected parameter was heart rate variability on deep breathing in34 (100%).In the ECG, out of 33 patients with definite CAN, corrected QT interval (QTc) was prolonged in 24 (73%) patients. Conclusion: Evaluation of cardiovascular reflexes constitute an important feasible and bedside clinical technique to detect CAN at earliest. QTc interval prolongation in ECG can be used for early diagnosis of CAN in busy outdoor setting. [Archana G NJIRM 2017; 8(4):68-72]